I often wonder how we get a root of a quadratic equation by putting a formula

\(x\quad =\quad \frac { -b\quad \pm \quad \sqrt { { b }^{ 2 }-4ac } }{ 2a } \)

But can anyone tell me the proof of this, this might be interesting, isn't it? Also, I would be pleased to know the proof of the GP series to infinity. Hey, you can also share some more interesting proofs which I would love to learn.

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestLet the equation be \( ax^2 + bx + c = 0 \)

Then \( x^2 + \frac{bx}{a} + \frac{c}{a} = 0 \)

\( x^2 + \frac{bx}{a} + \frac{b^2}{4a^2} - \frac{b^2}{4a^2} + \frac{c}{a} = 0 \)

\( (x + \frac{b}{2a})^2 = \frac{b^2}{4a^2} - \frac{c}{a} \)

\( (x + \frac{b}{2a})^2 = \frac{b^2 - 4ac}{4a^2} \)

\( x + \frac{b}{2a} = \sqrt{\frac{b^2 - 4ac}{4a^2}} \)

\( x + \frac{b}{2a} = \frac{\pm \sqrt{b^2 - 4ac}}{2a} \)

\( x = - \frac{b}{2a} + \frac{\pm \sqrt{b^2 - 4ac}}{2a} \)

\( x = \frac{ -b \pm \sqrt{b^2 - 4ac}}{2a} \)

My advice. Get NCERT Math books of higher classes. It'll contain most if not all of the basic proofs.

Log in to reply

Thanks for your advice! And ye, thanks for the proof, also.

Log in to reply

Um the quad equation proof can be done using squares.

Log in to reply

tell me the whole procedure, how?

Log in to reply

also, the GP series proof, any?

Log in to reply